2013
DOI: 10.1016/j.bbmt.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Second Hematopoietic Cell Transplantation in Myeloma

Abstract: Autologous hematopoietic cell transplantation (AHCT) as initial therapy of patients with multiple myeloma (MM) improves survival. However, data to support this approach for relapsed/progressive disease after initial AHCT (AHCT1) are limited. Using Center for International Blood and Marrow Transplant Research data, we report the outcomes of 187 patients who underwent a second AHCT (AHCT2) for the treatment of relapsed/progressive MM. Planned tandem AHCT was excluded. Median age at AHCT2 was 59 years (range, 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 31 publications
7
73
2
3
Order By: Relevance
“…[101][102][103] The primary endpoint is safety and tolerability, and an important secondary endpoint is an intrapatient comparison of time to progression (TTP) after salvage auto-HCT+CART19 cells to TTP after first auto-HCT. As TTP after salvage auto-HCT is typically significantly shorter than after first auto-HCT, 104,105 any improvement in this expected TTP would provide a preliminary signal of efficacy that would support additional studies in larger numbers of patients.…”
Section: Car T Cellsmentioning
confidence: 90%
“…[101][102][103] The primary endpoint is safety and tolerability, and an important secondary endpoint is an intrapatient comparison of time to progression (TTP) after salvage auto-HCT+CART19 cells to TTP after first auto-HCT. As TTP after salvage auto-HCT is typically significantly shorter than after first auto-HCT, 104,105 any improvement in this expected TTP would provide a preliminary signal of efficacy that would support additional studies in larger numbers of patients.…”
Section: Car T Cellsmentioning
confidence: 90%
“…This study provides evidence for the efficacy of salvage HDT-SCT compared with salvage cyclophosphamide (not a common treatment choice), essentially comparing 2 alkylator regimens in RRMM patients. Another large retrospective registry study 71 reported risk of progression of 51%, 82%, and 91% at 1, 3, and 5 years, respectively. These analyses were done at the time when the currently FDA-approved newer agents (CFZ, POM) were unavailable and the role of maintenance therapies with LEN and BTZ was not yet established.…”
mentioning
confidence: 98%
“…HDT-SCT2 may be a reasonable option to consider for young transplant-eligible patients with good performance status (PS) who derived a long PFS after HDT-SCT1. Among patients not receiving maintenance therapies after HDT-SCT, if the relapse is beyond the expected PFS (18-23 months), [71][72][73] HDT-SCT2 is an option to consider. For patients who have relapsed while receiving maintenance therapy, and the duration of remission is beyond the expected PFS (39-41 months for LEN maintenance 72,73 and 35 months for BTZ maintenance), 74 HDT-SCT2 may also be offered.…”
mentioning
confidence: 99%
“…Although median event free survival was longer for patients treated with early ASCT (39 mo vs 13 mo) the median OS was not significantly different between the two groups (64.6 mo vs 64 mo, P = 0.92), and 90% of the patients randomised to the VMPC arm were able to receive the planned delayed ASCT at the time of relapse [25] . Several analyses, summarised in Table 3, have investigated the role of ASCT as a salvage therapy for MM [29,[44][45][46][47][48][49][50][51] . These works are not always comparable, due to the different nature of the works (both prospective and retrospective) and to the fact that ASCT was …”
Section: Delayed Transplantationmentioning
confidence: 99%
“…Cook et al [49] 2011 106 Retrospective 19 mo (relapse from first transplant) Yes 63% NR 37 Jimenez-Zepeda et al [51] [45] 2013 187 Retrospective 32 mo Yes 68% 5% at 5 yr 29% at 5 yr Shah et al [68] Brioli A. ASCT in MM in some cases given as a salvage treatment after a previous ASCT [44][45][46] , whilst in others patients received ASCT after relapsing from a treatment not including transplantation [29,47,48] . One of the biggest records is the one published by Sellner et al [44] , in which 200 MM patients retreated with ASCT at the time of relapse were retrospectively analysed.…”
Section: Orr (%) Pfs (Mo) Os (Mo)mentioning
confidence: 99%